Retinal Vascular Tortuosity in a Patient with Weill-Marchesani Syndrome - Kevin Gallagher; Tahrina Salam; Barron Sin; Sandy Gupta; Hadi Zambarakji (Case Reports in Ophthalmological Medicine)
Weill-Marchesani syndrome (WMS) is a rare connective tissue disorder with characteristic phenotypic skeletal and ocular manifestations. A 28-year-old myopic female presented with an 8-month history of bilateral blurred vision. On examination, she was noted to be of short stature with brachydactyly. On ocular examination, she was found to be spherophakic with bilateral inferiorly subluxated lenses. Serum and urine homocysteine were normal and a syphilis screen was negative. A diagnosis of Weill-Marchesani syndrome was made. Fundoscopy revealed bilateral tortuous retinal vessels. We report the first illustrated case of retinal vascular tortuosity as an ocular manifestation of Weill-Marchesani syndrome.